Determination of Sintering Temperature Decrement by Improving Samarium Doped Ceria (SDC) based solid oxide fuel cell (SOFC) Electrolyte Through Rice Husk Silica (RHS) - Fatiha, Aleeza; Azmi, Mohd Azham (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This research effort addresses the effects of rice husk silica (RHS) on the sintering temperature of samarium-doped ceria (SDC)-based solid oxide fuel cell (SOFC) electrolytes since the high operating temperature is quite high. By combining RHS, this research hopes to improve the electrolytes’ thermal stability and conductivity. The procedure involves developing SDC-based electrolytes with different weight percentages of RHS and SDC which are 97:3, 98:2 and 99:1, followed by systematic sintering at detailed temperatures such as 1000°C,1100°C and 1200°C. The outcomes of this research involve improved SOFC performance and efficiency, an increasingly homogeneous microstructure with fewer flaws, greater structural integrity, electrolyte lifespan, increased porosity and unity, and improved ionic conductivity and mechanical reliability. These technological breakthroughs in sintering, SEM, and FTIR are expected to improve SOFC efficiency and applications.